Dimensões positivas de trabalho no Hucam - Viana, Leonardo Ferreira (2019)
At Brazil, a large part of the population use, mainly, the Sistema Único de Saúde (SUS). In this context, hospitals, mainly the public ones, are present to help the population at the moment they most need. The Academic Hospital Cassiano Antônio Moraes - Hucam appears as the only federal academic hospital in Espírito Santo state, being a key agent for the formation of health professionals and for the population. In this context, considering their noble finalistic activity, the aspects that impact the quality of life of their employees deserves special attention of their managers and, the diagnosis is a relevant way to demonstrate employees perception of certain work factors. The aim of this study was to make a research about organizational factors and work in Hucam, relating the labor link, estatutário (RJU) and celetista (CLT), and the activity area, end-activity and middle-activity, with the welfare at work, job engagement and job involvement constructs. The research, with quantitative approach, is characterized as descriptive and exploratory. The data collection process took place both through presencial collect, using a paper questionnaire as with online collect, using online questionnaire, with a sample of 160 professionals. As instruments, were used a sociodemographic questionnaire, a welfare at work scale, an engagement at work scale and an involvement at work scale. The analysis of the collected data was made with the MInitab 19 software, using Student's t parametric hypothesis test and Mann-Whitney non-parametric hypothesis test, to compare the stratified groups and their relationship with the constructs. It was concluded that when analyzing the area of activity as a subgroup within each labor link, there is a difference between them, being, overall, the score of the middle-activity - RJU higher than that score of the end-activity RJU and of the middle-activity - CLT. The end-activity – CLT score was higher than the middle-activity - CLT and the end-activity – RJU score. Overall, the perception of the professionals revealed a negative trend, reflecting low and medium scores.